Photoluminescence properties of Ce3＋ and Mn2＋-activated Ba9Sc2Si6O24 phosphor for white light emitting diodes - 边柳 王婷 宋振 刘朝晖 李嘉旭 刘泉林 (中国物理B：英文版, 2013)
A single-phased silicate compound （Ba1-xCex）9（Sc1-yMny）2Si6O24 was prepared by solid-state reaction at high temperature. From powder X-ray diffraction （XRD） analysis, the formation of Ba9Sc2Si6O24 with an R3 space group was confirmed. In the photoluminescence spectra under ultraviolet （UV） ray excitation, the Ba9Sc2Si6O24：Ce3＋,Mn2＋ phosphor emits two distinctive color light bands： a blue one originating from Ce3＋and a red one caused by Mn2＋. The energy transfer process from Ce3＋ to Mn2＋ was confirmed, the critical radius as well as the transfer efficiency was calculated, and the energy transfer mechanism was discussed. In addition, the decay-time testing indicates that the energy transfer efficiencies from Ce（1） to Mn2＋ and Ce（2） to Mn2＋ are different. The emission chromaticity of Ba9Sc2Si6O24：Ce3＋,Mn2＋ phosphor could be tuned from blue to red by altering the Ce3＋/Mn2＋ concentration ratio.